Project x: alian invaders - Brownlow, Mike (Oxford University Press Karachi, 2009)
Project X is a series of children's books designed to promote reading skills and literacy among early learners. The series features a variety of engaging stories across different genres, aimed at capturing children's imaginations and fostering a love for reading. Each book typically includes colorful illustrations and relatable characters, often incorporating themes of adventure, friendship, and discovery. Project X is often used in educational settings to support reading development through its structured approach and diverse content, making it appealing for both teachers and parents.